Ambient Temperature Drying Shrinkage and Cracking in Metakaolin-Based Geopolymers - Kuenzel, Carsten; Vandeperre, Luc J.; Donatello, Shane; Boccaccini, Aldo R.; Cheeseman, Chris (Journal of the American Ceramic Society, 2012)
Ambient temperature drying shrinkage in metakaolin-based geopolymer pastes exposed to low relative humidity environments has been investigated. The effect of varying the geopolymer composition (water content, Si:Al ratio, Na:Al ratio, and Na + or K + cations) on the sensitivity to ambient temperature drying shrinkage is reported. The definition of " structural" water as being the minimum water content required that prevents contractions in the gel structure, and thus drying shrinkage from occurring, is introduced. From the results presented, it is clear that the ionic charge density of cations, the total quantity of cations, and the relative quantities and stabilities of cation: AlO 4 - pairs in the paste are major factors affecting the sensitivity of pastes to ambient temperature drying shrinkage. © 2012 The American Ceramic Society.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.ambien